Loss-of-function variants in the filaggrin gene are a significant risk factor for peanut allergy. - IRVINE, ALAN (My University, 2011)
Background IgE-mediated peanut allergy is a complex trait with strong heritability, but its genetic basis is currently unknown. Loss-of-function mutations within the filaggrin gene are associated with atopic dermatitis and other atopic diseases; therefore, filaggrin is a candidate gene in the etiology of peanut allergy. Objective To investigate the association between filaggrin loss-of-function mutations and peanut allergy. Methods Case-control study of 71 English, Dutch, and Irish oral food challenge–positive patients with peanut allergy and 1000 non peanut-sensitized English population controls. Replication was tested in 390 white Canadian patients with peanut allergy (defined by food challenge, or clinical history and skin prick test wheal to peanut ≥8 mm and/or peanut-specific IgE ≥15 kUL−1) and 891 white Canadian population controls. The most prevalent filaggrin loss-of-function mutations were assayed in each population: R501X and 2282del4 in the Europeans, and R501X, 2282del4, R2447X, and S3247X in the Canadians. The Fisher exact test and logistic regression were used to test for association; covariate analysis controlled for coexistent atopic dermatitis. Results Filaggrin loss-of-function mutations showed a strong and significant association with peanut allergy in the food challenge–positive patients (P = 3.0 × 10−6; odds ratio, 5.3; 95% CI, 2.8-10.2), and this association was replicated in the Canadian study (P = 5.4 × 10−5; odds ratio, 1.9; 95% CI, 1.4-2.6). The association of filaggrin mutations with peanut allergy remains significant (P = .0008) after controlling for coexistent atopic dermatitis. Conclusion Filaggrin mutations represent a significant risk factor for IgE-mediated peanut allergy, indicating a role for epithelial barrier dysfunction in the pathogenesis of this disease.
PUBLISHED
Keywords: Atopic dermatitis; Immunology, Inflammation & Infection